Exploring the Phenomenon of Customers' Desired Value Change in a Business-to-Business Context - Flint, Daniel J.; Woodruff, Robert B.; Gardial, Sarah Fisher (Journal of Marketing, 2002)
Increasingly, organizations are pushed to adopt customer value strategies in order to grow profits and ensure long-term survival. Yet little is known about the dynamic nature of how customers perceive value from suppliers. The authors present findings from a grounded theory study conducted in a business-to-business context that sheds light on the nature of customers' desired value change and related contextual conditions. The authors discover that the phenomenon of customers' desired value change typically occurs in an emotional context, as managers try to cope with feelings of tension. The phenomenon extends well past the change itself into strategies customers use to motivate suppliers to meet their changed needs. Customers' value change provides a reason for customers to seek, maintain, or move away from relationships with suppliers.